Antibacterial activity of phenyllactic acid against Listeria monocytogenes and Escherichia coli by dual mechanisms. (1st August 2017) - Ning, Yawei; Yan, Aihong; Yang, Kun; Wang, Zhixin; Li, Xingfeng; Jia, Yingmin
Highlights: Antibacterial mechanism of phenyllactic acid against Escherichia coli was elucidated. Dual antibacterial targets were proposed, namely cell membrane and genomic DNA. This study may help in explaining the biopreservation effect of lactic acid bacteria. Abstract: Phenyllactic acid (PLA), a phenolic acid phytochemical, is considered to be a promising candidate for use as a chemical preservative due to its broad antimicrobial activity. The antibacterial target of PLA has rarely been reported, thus investigations were performed to elucidate the antibacterial mechanism of PLA against Listeria monocytogenes and Escherichia coli . Flow cytometry analysis stained with propidium iodide (PI) demonstrated that PLA could damage the membrane integrity of L. monocytogenes, while it could not disrupt that of E. coli . The uptake of 1- N -phenylnaphthylamine (NPN) indicated that PLA interrupted the outer membrane permeability of E. coli . Scanning electron microscopy (SEM) observation visualized the damage caused by PLA as morphological changes in L. monocytogenes and E. coli. Fluorescence assays demonstrated that PLA could interact with bacterial genomic DNA in the manner of intercalation. This finding suggested dual antibacterial targets of PLA, namely membrane and genomic DNA.